(untitled) (CIPEEX, 2025)
This work analyzes the articulation between public policy cycles and the structural process generated by the Claim of Non-Compliance with a Fundamental Precept (ADPF) 347, treating it as a paradigmatic case of judicial intervention in the face of governmental omission. The objective is to explain how the judiciary, through ADPF 347, not only recognized the severe violations of rights in the Brazilian prison system but also compelled the formulation of public policies to address them. The methodology integrates the theoretical frameworks of public policy studies with the legal and constitutional analysis of the ADPF, focusing on the stages of policy development from problem identification to implementation and evaluation. The results indicate that the Supreme Federal Court’s decision redefined the political agenda by forcing the executive and legislative branches to adopt measures such as custody hearings, the national prison plan “Pena Justa,” and regional adaptations in the states. This judicial imposition transformed abstract constitutional principles into enforceable public policies, generating significant institutional recomposition. The work concludes that ADPF 347 exemplifies the judiciary’s capacity to act as a guardian of constitutional rights by stimulating the design, execution, and monitoring of public policies, while also raising questions about the balance of powers and the legitimacy of judicial activism in contexts of persistent social crisis.